2017
DOI: 10.1016/j.asr.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the eccentricity of the primaries in powered Swing-By maneuvers

Abstract: The present paper studies the powered Swing-By maneuver when performed in an elliptical system of primaries. It means that there is a spacecraft travelling in a system governed by the gravity fields of two bodies that are in elliptical orbits around their center of mass. The paper particularly analyzes the effects of the parameters relative to the Swing-By (V inf À ; r p ; w), the orbit of the secondary body around the primary one (e; m) and the elements that specify the impulse applied (dV ; a) to the spacecr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In a sequence, Casalino et al (1999a) expanded this analytical study to cover the situation where the impulse is applied in different points of the trajectory. There are several other works considering the study of the swing-by maneuver combined with an impulse in the spacecraft based on numerical integration (Prado 1997;Casalino et al 1999b;Santos et al 2008;Silva et al 2013;Ferreira et al 2015Ferreira et al , 2017aFerreira et al , 2017bFerreira et al , 2017cPiñeros and Prado 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sequence, Casalino et al (1999a) expanded this analytical study to cover the situation where the impulse is applied in different points of the trajectory. There are several other works considering the study of the swing-by maneuver combined with an impulse in the spacecraft based on numerical integration (Prado 1997;Casalino et al 1999b;Santos et al 2008;Silva et al 2013;Ferreira et al 2015Ferreira et al , 2017aFerreira et al , 2017bFerreira et al , 2017cPiñeros and Prado 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the objective of the present paper is to make an analytical study of the pure gravity swing-by maneuver (without impulse), presenting the equations for the velocity, energy and angular momentum variation as functions of the basic parameters of the swing-by, for systems where the primary bodies are in elliptical orbits. Prado (1997) and Ferreira et al (2017a) performed numerical studies for systems in elliptical orbits, using the elliptic restricted three body problem, but in both cases considering also an impulsive maneuver. Those studies showed interesting aspects of the problem, indicating the necessity of making analytical studies for the elliptical case, similar to those available for the circular problem.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an even higher eccentric system in the Solar System is the dwarf planet Haumea, which has a moon with an eccentricity close to 0.25 (Sanchez et al 2016). A first study of maneuvers in eccentric systems is shown in Prado (1997), which studied the pure gravity Swing-By maneuver (without impulses) for the elliptic case and Ferreira et al (2017cFerreira et al ( , 2017a, which made a numerical study of the powered Swing-By maneuver, with the impulse applied at the periapsis of the orbit of the spacecraft around the secondary body of the system and in different directions, considering the two main bodies in elliptical orbits. An analysis of the effect of the eccentricity was presented in these papers, besides the study of the maximum gains and losses of energy obtained from the maneuver.…”
Section: Introductionmentioning
confidence: 99%
“…If an impulsive maneuver is applied during the GAM, the direction of the impulse works as one more control for the maneuver, changing the effects of the GA. As a negative point, this powered maneuver requires the use of a space propulsion system, resulting in fuel consumption, and so increasing the cost of the mission. The possible uses of this powered maneuver have been analyzed for planets and moons of the solar system [17][18][19][20][21][22][23][24]. When the maneuver is made close to planets that have significant atmosphere and using a spacecraft with wing-body shape (waverider), the AGAM could also be controlled by the direction and/or magnitude of the aerodynamic forces generated during atmospheric flight [2][3][4][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…In that sense, the present paper has the goal of studying a new version of this maneuver, where the bank angle is assumed to be variable and constituting in a new form to control the AGAM and PAGAM, which was not used before. The mathematical model selected to analyze the applications of the maneuvers and the resulting trajectories around the center of mass of the orbital system is the circular restricted three-body problem (CRTBP) [36], which is highly accepted in this kind of problems [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The choice of this model is based on our solar system, where the massive body is the sun, the secondary body is a planet with atmosphere used for the maneuver, and the third body is the spacecraft, represented as a massless waverider.…”
mentioning
confidence: 99%